Comparative study of gyrokinetic, hybrid-kinetic and fully kinetic wave physics for space plasmas. (29th June 2016) - Told, D; Cookmeyer, J; Muller, F; Astfalk, P; Jenko, F
Abstract: A set of numerical solvers for the linear dispersion relations of the gyrokinetic (GK), the hybrid-kinetic (HK), and the fully kinetic (FK) model is employed to study the physics of the KAW and the fast magnetosonic mode in these models. In particular, we focus on parameters that are relevant for solar wind oriented applications (using a homogeneous, isotropic background), which are characterized by wave propagation angles averaging close to 90°. It is found that the GK model, while lacking high-frequency solutions and cyclotron effects, faithfully reproduces the FK Alfv\acute{e}n wave physics close to, and sometimes significantly beyond, the boundaries of its range of validity. The HK model, on the other hand, is much more complete in terms of high-frequency waves, but owing to its simple electron model it is found to severely underpredict wave damping rates even on ion spatial scales across a large range of parameters, despite containing full kinetic ion physics.